PENGARUH STRUKTUR MODAL DAN KINERJA OPERASIONAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN ASURANSI DI INDONESIA - Sumarlan, Ahmad (Universitas Muhammadiyah Bengkulu, 2024)
Indonesia is a developing country with a large population and a relatively high level of economic growth, it has companies that perform well in various sectors but still vary in each economic sector. Performance as measured by the company's profitability will influence the company's condition. Large profits cannot be separated from the company's financial decisions. one of them is funding decisions. The funds obtained can come from debt and equity to form the company's capital structure. This research aims to examine the influence of capital structure and operational performance on financial performance. The data used is secondary data obtained from annual reports and financial reports accessed via idx.co.id. The independent variables are capital structure which is measured using the Debt Equity Ratio (DER) and operational performance which is measured using liquidity. The dependent variable in this research uses financial performance as measured by Return On Assets (ROA). The results prove that: (1) capital structure has a positive and significant effect on financial performance. (2). Operational performance has a negative and significant effect on financial performance. Keywords: Capital Structure, Operational Performance, Financial Performance